The Role of Citizenship Education on Enhancing the Promotion of Unity in Nigeria: Implication for Primary Education - Ann Ngozi Ugobueze (Journal of Education and Teacher Training Innovation, 2024)
Citizenship education, as a pedagogical approach, emphasizes the development of civic responsibility, tolerance, and national identity, which are essential for addressing the challenges posed by Nigeria's ethnic, cultural, and religious diversity. The study explores how the integration of citizenship education in primary schools helps inculcate values such as respect for diversity, patriotism, and conflict resolution skills among young learners.  Using a survey research design, data were collected from 320 Nigeria Certificate in Education (NCE) students from Nwafor Orizu College of Education, Nsugbe, and Federal College of Education (Technical), Umunze, in Anambra State, Nigeria. Purposive random sampling was employed to select respondents from Social Studies, Economics, English, and Igbo Language departments. A structured questionnaire with 15 items on a 4-point Likert scale was used for data collection, and reliability was confirmed using the Pearson Product Moment Correlation Coefficient. Data analysis involved mean scores, with a cutoff of 2.50 for agreement. Findings revealed that ethnic hatred, religious intolerance, distrust, lack of basic education, and colonial policies are significant barriers to unity in Nigeria. Citizenship education was found to promote unity by enhancing the appreciation of diversity, instilling values of cooperation and tolerance, and equipping individuals with conflict resolution skills. However, challenges such as a lack of qualified teachers, insufficient instructional materials, and inadequate commitment from educators hinder its effectiveness. The findings highlight the importance of incorporating citizenship education into primary education to cultivate values that promote unity among young learners. The research findings imply the need for systematic transformation in the basic education curriculum, by integrating programs that comprehensively teach the values ​​of tolerance, cooperation, and conflict resolution.